EVALUASI JURNAL ILMIAH - Karnadi Karnadi; Ika Lestari (Perspektif Ilmu Pendidikan, 2009)
A scientific journal is needed as a medium in publishing the research findings which can be beneffited not only as an information to increase the knowledge but also as a reference for future researchers. The quality of the scientific journal, therefore, should be guaranteed from certain aspects such as the content, language, style, and periode . This evaluation research aimed at measing the quality of scientific journal published by The School of Education, State University of Jakarta, titled Jurnal Perspektif Ilmu Pendidikan based on the standards formulated by LIPI. The evaluation used quantitative approach and took place in The School of Education, State University of Jakarta, Penelitian ini menggunakan pendekatan kuantitatif. Tempat penelitian yaitu di Fakultas Ilmu Pendidikan Universitas. The evaluation, conducted as from April through October 2009, covered all publications of 2006 - 2009. The result of the evaluation showed a number of requirements in puplising a scientific journlal based on LIPI standards, have not fulfilled, To be accredited as a scientific journal, this evaluation pointed out some steps to be taken by the editorial board of Jurnal Perspektif Ilmu Pendidikan.